Expression of positive emotions differs in illness and recovery in anorexia nervosa. (30th December 2016) - Dapelo, Marcela Marin; Hart, Sharon; Hale, Christiane; Morris, Robin; Tchanturia, Kate
Abstract: People with Anorexia Nervosa (AN) display reduced facial expression of emotions. This study investigated the expression of positive affect in response to a film, examining Duchenne and non-Duchenne smiles in 20 women who have recovered from AN (REC), 20 with acute AN and 20 healthy controls (HC). The results indicated that the REC group exhibited Duchenne and non-Duchenne smiles with higher duration and intensity than the AN group, comparable to the HC group. The findings warrant longitudinal studies to confirm that reduced expressivity is linked to acute AN, ameliorating after recovery. Highlights: The facial expression of women recovered from anorexia nervosa (REC) was studied. REC smiled more than acutely ill participants in response to a positive film. The facial expression of REC was similar to the healthy controls. Facial expressivity in REC was not related to depression or anxiety.